Respuestas Judiciales a la Violencia de Género: el Derecho como Discurso y Práctica Sociales = Judicial Responses to Gender-based Violence : the Law as Discourse and Social Practice - Busso, Mariana N. Sánchez (Oñati Socio-Legal Series, 2015)
Usually the studies on the legal system are limited to normative or jurisprudential analysis. However, long time ago, we know that to understand to the law needs to know its meanings, its previous values and also its speeches and practices; this is, to understand it like a social phenomenon. Social phenomenon that involves and expresses much more than a set of rules. This is an idea that not only comes from the Sociology of Law, but the feminist legal theories have incorporated too. Within this theoretical framework, the law can be understood as a powerful social discourse that gives meaning to the behavior of men and women. So, the social construction of roles, social positions and the relationship between the genres, can be best understood if it considers the contribution offered by the laws, institutions, systems, and also speeches and speaking of judges through their sentences. As well, and within this context of ideas, this work aims to understand and analyze how it is constructed and expresses from the voice of the judges themselves, the social phenomenon of gender violence; his speeches, his conceptualizations, its legitimacy; by means of the analysis of the judgments in which they express their own voice.